Defamiliarization in the Novel Charlie and the Chocolate Factory - Cita Hikmah Yanti (UNMUH BABEL PRESS, 2020)
Language used in literary works is commonly dif erent from language used in daily or ordinary language. Therefore, Russian Formalists introduced defamiliarization, in which it is known to be a technique to create or to see dif erences of literary languages and ordinary languages. In this study, researcher defined the technique of defamiliarization in the novel Charlie and the Chocolate Factory by Roald Dahl, with the intention to find the ef ects of defamiliarization in the novel. In conducting the study, researcher used qualitative method, because the researcher collected the data from sentences which showed strange or unfamiliar ideas, objects, and situations in the story of the novel. The result of this study showed that defamiliarization is used in the novel and it gave the ef ects of defamiliarization to the novel, especially at the level of perception, language, narrative structure, genre, as well as the literariness and aesthetic quality of the language in the novel.